Grid Implementation of Parallel Algorithm for Laplacean Equation Computation by Jacobi Iteration Method - Hanuliak, Peter; Varsa, Peter (Communications - Scientific letters of the University of Zilina, 2003)
The article is devoted to the problem of parallel algorithms and their practical implementations. On the basis of parallel computer analysis in the world the parallel systems are divided into two basic groups – synchronous and asynchronous systems – which are very different from the system point of view. This article describes the development of real parallel algorithms for Jacobi iteration. This individual practical example demonstrates the influence of decomposition strategies for performance evaluation of parallel Jacobi iteration and discusses the ways for their parallel implementations.